Effectiveness of a real-life program (DIAfit) to promote physical activity in patients with type 2 diabetes: a pragmatic cluster randomized clinical trial - Arhab, Amar; Junod, Nicolas; Rossel, Jean-Benoit; Giet, Olivier; Sittarame, Frederic; Beer, Sandra; Sofra, Daniela; Durrer, Dominique; Delgado, Humberto; Castellsague, Montserrat; Laimer, Markus; Puder, Jardena J. (Frontiers in Endocrinology, 2023)
Introduction: The aim of this study was to evaluate the effectiveness of a real-life clinical physical activity program (DIAfit) on improving physical fitness, body composition, and cardiometabolic health in an unselected population with type 2 diabetes mellitus, and to compare the effects of two variants with different exercise frequencies on the same outcomes. Research design and methods: This was a cluster randomized-controlled assessor-blind trial conducted in 11 clinical centres in Switzerland. All participants in the clinical program with type 2 diabetes were eligible and were randomized to either standard (3 sessions/week for 12 weeks) or alternative (1 session/week for the first four weeks, then 2 sessions/week for the rest of 16 weeks) physical activity program each consisting of 36 sessions of combined aerobic and resistance exercise. Allocation was concealed by a central office unrelated to the study. The primary outcome was aerobic fitness. Secondary outcome measures included: body composition, BMI, HbA1c, muscle strength, walking speed, balance, flexibility, blood pressure, lipid profile. Results: A total of 185 patients with type 2 diabetes (mean age 59.7 ±10.2 years, 48% women) were enrolled in two groups: standard group (n=88) and alternative group (n=97). There was an 11% increase in aerobic fitness after the program (12.5 Watts; 95% CI 6.76 to 18.25; p<0.001). Significant improvements in physical fitness, body composition, and cardiometabolic parameters were observed at the end of the DIAfit program (improvements between 2-29%) except for lean body mass, triglycerides and cholesterol. No differences were observed between both programs, except for a larger weight reduction of -0.97kg (95% CI -0.04 to -1.91; p=0.04) in the standard program. Conclusions: Both frequency variants of the nation-wide DIAfit program had beneficial effects on physical fitness, HbA1c, body composition, and blood pressure in type 2 diabetes patients and differences are negligible.